Human Creation Between Reality and Illusion - Tymieniecka, Anna-Teresa (Analecta Husserliana, The Yearbook of Phenomenological Research, 2005)
Identifying quickly illusion with deception, we tend to oppose it to the reality of life. However, investigating in this collection of essays illusion's functions in the Arts, which thrives upon illusion and yet maintains its existential roots and meaningfullness in the real, we might wonder about the nature of reality itself. Does not illusion open the seeming confines of factual reality into horizons of imagination which transform it? Does it not, like art, belong essentially to the makeup of human reality? Papers by: Lanfranco Aceti, John Baldacchino, Maria Avelina Cecilia Lafuente, Jo Ann Circosta, Madalina Diaconu, Jennifer Anna Gosetti-Ferencei, Brian Grassom, Marguerite Harris, Andrew E. Hershberger, James Carlton Hughes, Lawrence Kimmel, Jung In Kwon, Ruth Ronen, Scott A. Sherer, Joanne Snow-Smith, Max Statkiewicz, Patricia Trutty-Coohill, Daniel Unger, James Werner.